Irony as a Means of Characteristics in the Works of A. P. Chekhov - Qodirova N. A (International Journal on Orange Technologies, 2021)
This article discusses the irony as a conceptual category of artistic text, which enters the author's assessment in implicit form. An ironic meaning as an integral component of the artistic text is an estimated emotional method of representation of the worldview and the values ​​of the author. The means of explication of irony in the works of A.P. Chekhov of various genre affiliation (epic, dramaturgical genres). Similarities and differences are established in using author’s infection of irony in a number of works. Irony as a means of characteristics in the works of A.P. Chekhov "Chameleon", "horsepower", "Nalim", "Agafya", "Grisha", "Nightmare", "Seagull", "Cherry Garden", with the author's ironic characteristics of the characters. It is concluded that the genre features of the artwork affect the use by the author’s ironic expression.